2003
DOI: 10.1113/jphysiol.2002.032045
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at the GABA receptor selectivity filter: a possible role for effective charges

Abstract: An important feature of ligand-gated ion channels is their exquisite ability to discriminate between ions. Still, little is known about the mechanisms underlying, or structural determinates of, this ability. We examined the structural elements underlying the ionic selectivity of rho1 GABA receptors expressed in Xenopus oocytes and human embryonic kidney cells using site-directed mutagenesis and two-electrode voltage-clamp or patch-clamp techniques. The wild-type GABA receptor was chloride selective, with a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 36 publications
4
55
1
Order By: Relevance
“…Also, in this channel it was possible to directly change the charge at position 0 . Neutralizing this charge made it slightly less anion-selective than the WT GABA Rs, but it still remained anion-selective, whereas replacing the positive charge with a negative one R E did make the channel weakly cation-selective P P [35]; see also discussion in [7]. Recently it has also been shown that placing a negative charge in the 2 position in the GABA R (a single mutation of the 2 proline to a glutamate P E) did invert its charge selectivity from being anion-selective P P to cation-selective (with P P ) [36].…”
Section: Recent Measurements In Othermentioning
confidence: 89%
“…Also, in this channel it was possible to directly change the charge at position 0 . Neutralizing this charge made it slightly less anion-selective than the WT GABA Rs, but it still remained anion-selective, whereas replacing the positive charge with a negative one R E did make the channel weakly cation-selective P P [35]; see also discussion in [7]. Recently it has also been shown that placing a negative charge in the 2 position in the GABA R (a single mutation of the 2 proline to a glutamate P E) did invert its charge selectivity from being anion-selective P P to cation-selective (with P P ) [36].…”
Section: Recent Measurements In Othermentioning
confidence: 89%
“…The residue at position 2′ has been shown to influence response kinetics, ion permeability, selectivity and conductance of the GABA C receptors (Qian et al., 1999; Wotring et al., 2003, 2008; Carland et al., 2004a,b; Filippova et al., 2004; Zhu et al., 2007). Ginkgolide B has been shown by molecular modelling to be structurally similar to PTX (Ivic et al., 2003) and the ginkgolides only differ from one another in the hydroxyl substituents.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the pore tapered from 25 A on the extracellular side to 3 A on the intracellular side. The location of residues known to be involved in ion selectivity [59][60][61] are appropriately located in the TM1-2 loop (Fig. 2A).…”
Section: Geometry and Dimensionsmentioning
confidence: 98%